The Function Of Rivers For Society In The Short Story “Gagal Landing” By Achmad Supardi - Sugiarto, Septian Rifki; Anggraeni, Rezki Amelia (Journal of Language, Literature and Teaching, 2024)
Rivers, being an important element in human life, are often depicted in literary works. One of the literary works that depicts the relationship between rivers and society is the short story “Gagal Landing” by Achmad Supardi. First published in Jawa Pos on January 28th, 2018, the short story shows how the Brisbane River and the Martapura River contribute to the local society. This article explains the comparison of the functions of the Brisbane River in Australia and the Martapura River in Indonesia for society's daily lives. The approach used in this research is sociological literature with interpretive analysis as a data analysis technique. The results obtained show that the Brisbane River and Martapura River have an important role in society and can provide positive benefits for their lives. The Brisbane River functions as a place for pastime, relaxation, and gathering, as well as a waterway transportation route. Its existence can relieve stress, improve mental well-being, release tension, and provide the opportunity for urban society to enjoy moments of happiness. Meanwhile, the Martapura River functions as a waterway transportation route as well as a center for economic and social activities in the surrounding society because of the floating market. The floating market on the Martapura River plays an important role in maintaining and promoting local cultural and culinary heritage.